2010
DOI: 10.4103/0019-5049.68374
|View full text |Cite
|
Sign up to set email alerts
|

We should care more about intracuff pressure: The actual situation in government sector teaching hospital

Abstract: Endotracheal tube (ETT) should have intracuff pressure (ICP) in the range of 20 to 30 cm water (H2O). In this observational study, we studied the trend amongst anaesthesiologist in choosing the type of ETT and their ability to assess optimum ICP clinically. After institutional ethics committee approval, we observed 75 patients under general endotracheal anaesthesia in Government Medical College. Anaesthesiologists were blinded to study purpose. The type of ETT used and magnitude of ICP was recorded. ICP was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…A study conducted in Denmark showed a median ETT cuff pressure of 30 cm H₂O (range 8-100) compared with the median pressure of 36 cm H₂O (range 10-120) recorded in our study. 8 In our study 62 (64.58%) patients had ETT cuff pressures > 30 cm H₂O, compared with 50% in the American study, 5 45% of patients in the Danish study, 8 26.2% in the Indian study 6 and 23% in the Cape Town study. 7 Only 18 (18.75%) patients in our study had an ETT cuff pressure within the normal range whereas in the American study 27% of patients had normal ETT cuff pressures and in the Indian study 59% of ETT cuff pressures were normal.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…A study conducted in Denmark showed a median ETT cuff pressure of 30 cm H₂O (range 8-100) compared with the median pressure of 36 cm H₂O (range 10-120) recorded in our study. 8 In our study 62 (64.58%) patients had ETT cuff pressures > 30 cm H₂O, compared with 50% in the American study, 5 45% of patients in the Danish study, 8 26.2% in the Indian study 6 and 23% in the Cape Town study. 7 Only 18 (18.75%) patients in our study had an ETT cuff pressure within the normal range whereas in the American study 27% of patients had normal ETT cuff pressures and in the Indian study 59% of ETT cuff pressures were normal.…”
Section: Discussionmentioning
confidence: 45%
“…Mean ETT cuff pressure of 27.07 cm H₂O was recorded in a study conducted in a government teaching hospital in India. 6 Bernon et al 7 in 2013, in an academic hospital in Cape Town, reported a mean cuff pressure of 25 cm H₂O in anaesthetised patients. A study conducted in Denmark showed a median ETT cuff pressure of 30 cm H₂O (range 8-100) compared with the median pressure of 36 cm H₂O (range 10-120) recorded in our study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(5) Trivedi ve ark. (6) yaptıkları çalışmada; PVC tüplerle, kırmızı plastik (düşük volüm-yüksek basınç kaflı) çok kullanımlık tüp-leri karşılaştırdıklarında, PVC tüpler kullanıldığında da kaf içi basıncın manometre ile ölçülmesinin daha güvenli olduğu gös-terilmiştir.…”
Section: Discussionunclassified